2006
DOI: 10.1136/adc.2005.086306
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation of premature infants

Abstract: Premature infants are at increased risk of vaccine preventable infections, but audits have shown that their vaccinations are often delayed. Early protection is desirable. While the evidence base for immunisation of preterm infants is limited, the available data support early immunisation without correction for gestational age. For a number of antigens the antibody response to initial doses may be lower than that of term infants, but protective concentrations are often achieved and memory successfully induced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 78 publications
1
63
0
5
Order By: Relevance
“…n eonatal infections are a major contributor to neonatal death and many of those are avoidable by vaccination (1). Extreme-and very-low-birth-weight infants are at higher risk of suffering from infections than term newborns (2), such as influenza (3) or pneumococcal diseases (4).…”
mentioning
confidence: 99%
“…n eonatal infections are a major contributor to neonatal death and many of those are avoidable by vaccination (1). Extreme-and very-low-birth-weight infants are at higher risk of suffering from infections than term newborns (2), such as influenza (3) or pneumococcal diseases (4).…”
mentioning
confidence: 99%
“…Similarly, cytomegalovirus, Chlamydia spp., group B streptococci, and Haemophilus influenzae are important causes of neonatal pneumonia but do not normally cause pneumonia in adults. Despite the great need for vaccines that are effective in neonates, responses to vaccination are weak and usually ineffective in this age group (1,4).…”
mentioning
confidence: 99%
“…Unexpectedly, safety profile in terms of normal reactions to vaccines administered to premature and low-birth-weight children in comparison with term infants appeared different. The only possible exception is the increase in the rate of apnea (accompanied or not by bradicardia) and desaturation episodes, which is observed by most authors [12][13][14][15]. Observation of 473 premature infants of weight <1,500g (average weight -910g [375-1,495]), average GA of 27.6 (22.6-34.3) weeks and GA by the moment of vaccination of 37.4 (31.5-48.3) weeks showed that only 2.8% of children had generalized (fever) and local reactions; however, 10% of children had apneic episodes with/without bradicardia [16].…”
Section: Safety Of Vaccinesmentioning
confidence: 68%